2011
DOI: 10.1021/jm101423y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 6-(2,4-Difluorophenoxy)-2-[3-hydroxy-1-(2-hydroxyethyl)propylamino]-8-methyl-8H-pyrido[2,3-d]pyrimidin-7-one (Pamapimod) and 6-(2,4-Difluorophenoxy)-8-methyl-2-(tetrahydro-2H-pyran-4-ylamino)pyrido[2,3-d]pyrimidin-7(8H)-one (R1487) as Orally Bioavailable and Highly Selective Inhibitors of p38α Mitogen-Activated Protein Kinase

Abstract: The development of a new series of p38α inhibitors resulted in the identification of two clinical candidates, one of which was advanced into a phase 2 clinical study for rheumatoid arthritis. The original lead, an lck inhibitor that also potently inhibited p38α, was a screening hit from our kinase inhibitor library. This manuscript describes the optimization of the lead to p38-selective examples with good pharmacokinetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 20 publications
2
58
1
Order By: Relevance
“…Excessive osteoclast activity results in bone‐related disease, including postmenopausal osteoporosis, rheumatoid arthritis (RA), and Paget's disease . Here, we showed PAM, a novel selective p38 MAPK inhibitor, inhibits the formation and resorption of multinucleated osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive osteoclast activity results in bone‐related disease, including postmenopausal osteoporosis, rheumatoid arthritis (RA), and Paget's disease . Here, we showed PAM, a novel selective p38 MAPK inhibitor, inhibits the formation and resorption of multinucleated osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…(14,15) However, it is still interesting whether p38 inhibitors, particularly selective inhibitors, can be used for the treatment of osteolytic diseases such as osteoporosis. Indeed, a selective p38 inhibitor, pamapimod (PAM), (16) was previously used for the treatment of rheumatoid arthritis. (17) It was proven to be effective for the prevention of joint destruction with the underlying mechanisms needing further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Although inhibiting p38MAPK to enhance neuritogenesis may be a postnatal photoreceptor-specific phenomenon, it is possible that this is an "off-target" mechanism of the molecule, perhaps due to inhibition of one or more other kinases. Indeed, the kinase selectivity profile of the pyrimidinopyridone family from which this molecule was found demonstrates submicromolar inhibition of 10 out of the 300 kinases tested (Goldstein et al 2011). Future studies performed in a photoreceptor-specific systems pharmacology context may uncover currently unknown effects of similar small molecules on cellular phenotypes.…”
Section: Discussionmentioning
confidence: 94%
“…CHEMBL-1766490 is reported to have p38α MAPK inhibitory activity (Goldstein et al, 2011). It has been reported that p38α inhibition induces neuronal differentiation, whereas other reports suggest that neurite outgrowth is inhibited following p38α knockdown in PC12 and P19 committed neuronal cell lines (Morooka and Nishida, 1998; Iwasaki et al, 1999; Aouadi et al, 2006).…”
Section: X4 Discussionmentioning
confidence: 99%
“…Although inhibiting p38MAPK to enhance neuritogenesis may be a postnatal photoreceptor-specific phenomenon, it is possible that this is an “off-target” mechanism of the molecule, perhaps due to inhibition of one or more other kinases. Indeed, the kinase selectivity profile of the pyrimidinopyridone family from which this molecule was found demonstrates submicromolar inhibition of 10 out of the 300 kinases tested (Goldstein et al, 2011). Future studies performed in a photoreceptor-specific systems pharmacology context may uncover currently unknown mechanisms of actions of similar small molecules on cellular phenotypes.…”
Section: X4 Discussionmentioning
confidence: 99%